Utilization of Banana Peels as Active Carbon for Pollutant Removal in Wastewater: Review Analysis - Rofikoh, Vina; Zaman, Badrus; Prasetyo Samadikun, Budi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
Pollutants from human activities released into the environment, including heavy metals, dyes, and chemicals, can harm the environment and living organisms. One solution offered to treat these pollutants is an adsorption technique using activated carbon from banana peel waste. The research aims to review the potential of banana peel waste as active carbon to remove various contaminants in wastewater and highlight the opportunities and challenges. This research uses a systematic literature review method, or what is usually called a Systematic Literature Review (SLR), to collect data from the Google Scholar online article database and E-Journal at SSO Undip (Single Sign On). The results of the literature review show that active carbon from various types of banana peels, such as Musa Acuminata, Musa sp., Musa paradisiaca L., and Musa Acuminatabalbisiana has been proven to be able to remove organic materials, inorganic anions, heavy metals, dyes, and chemical compounds from wastewater.